Translocation Study of Some Zooxanthellae Clade to the Survival and Growth of Goniastrea aspera after Bleaching - Pujiono W. Purnomo (International Journal of Marine and Aquatic Resource Conservation and Co-existence, 2014)
Inter-host translocation technique of zooxanthellae was attempted to prove Buddemier and Futin’s (1993) theory on adaptation. The recent trend of coral products trading must be anticipated by its mass production through artificial techniques, the alternation of natural resources. Translocation bio-technique of zooxanthellae on coral was expected to resolve the problem and the translocation study should provide fundamental answer to coral recovery. The study of zooxanthellae translocation was proposed to: a) Evaluate the effect of zooxanthellae enrichment on its translocation on coral polyp tissue efter optimum bleaching and b) Investigate the effect of translocation on coral growth. The research was experimental, involving coral species Goneastrea aspera, and purified zooxanthellae clade A, B and C with circulating incubation condition in BPBBAP Jepara indoor area. The experiment took place for 30 weeks in both model environment waters and natural environment waters of Jepara Panjang Island coral area from March to August 2008. The result showed that: a) In the artificial waters, translocation zooxanthellae to polyp tissue of Goneastrea aspera occured at day 17 and more fast in the natural waters; b) In the controlling of temperature environment on translocation provided positive response of Goneastrea aspera’s normal life, relocation and growth rate of zooxanthellae as in nature and c) recognition, resettlement, and growth process of zooxanthellae made it possible for Goneastrea aspera to grow normally in natural waters. Key words: Clade, bleaching, recognition, resettlement, growth, translocation, zooxanthellae, Goneastrea aspera